Uji Karakteristik Briket Berbahan Baku Bonggol Jagung Berdasarkan Variasi Jumlah Perekat - Yogi Wahyudi; Shafwan Amrullah; Cyrilla Oktaviananda (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
Charcoal briquettes are a renewable form of energy from biomass. This briquette is an alternative to fossil fuels. In this study, the process of analyzing the effect of the amount of adhesive on the water content, index of destruction, ash content, and calorific value of corn cob briquettes was carried out. The use of tapioca flour adhesive concentrations of 0%, 3%, 5%, and 7%. This study used a completely randomized series or RAL for a single factor with ANOVA analysis to determine the effect of the use of various adhesives on corn cob briquettes. The results obtained were, 0% produced briquettes with values of moisture content, ash content, heating value, and destruction index were 0.19%, 0.14%, 0.19% and 5.655 Cal/gr, respectively. For 3% adhesive, the yield of moisture content, ash content, calorific value, and destruction index were 0.21%, 0.33%, 0.28% and 5.398 Cal/gr, respectively. At 5% adhesive concentration the test results of moisture content, ash content, calorific value, and destruction index were 0.22%, 0.35%, 0.34% and 4.431 Cal/gr, respectively. Meanwhile, the adhesive concentration of 7% was 0.31%, 0.89%, 0.38% and 3.382 Cal/gr, respectively. If this result is based on SNI, it can be said that it has met these standards.